Penerapan Model Vector Autoregression dalam Peramalan CAR dan ROA Bank BJB - Salsabila, Felisha; Teti Sofia Yanti (UNISBA Press, 2025)
Abstract. In facing increasingly complex economic dynamics, banks are expected to maintain their financial stability through the management of various financial indicators. Some of the key indicators include the Capital Adequacy Ratio (CAR) and Return on Assets (ROA). This study aims to analyze the dynamic relationship and forecast CAR and ROA at Bank BJB for the period 2016–2024 using the Vector Autoregression (VAR) model. The data used consists of quarterly financial reports of Bank BJB from 2016 to 2024, obtained from the official website of Bank BJB. The data is processed using EViews 10 software through several stages, including descriptive statistics, stationarity testing, cointegration testing, model estimation and stability testing, diagnostic checking, optimal lag determination, Granger causality testing, forecasting, and accuracy evaluation using the Mean Absolute Percentage Error (MAPE) value. The results show that two parameters are significant at the 10% level: ΔCAR(-2) on ΔCAR and ΔROA(-1) on ΔROA. The forecasting model in this study is able to capture the historical patterns of CAR and ROA quite well, as indicated by a MAPE value of 3.56% for CAR which is considered very good and 22.37% for ROA, which falls into the fair category. Abstrak. Dalam menghadapi dinamika ekonomi yang semakin kompleks, bank diharapkan menjaga stabilitas keuangannya melalui pengelolaan berbagai indikator keuangan. Beberapa indikator penting tersebut antara lain adalah Capital Adequacy Ratio (CAR) dan Return on Assets (ROA). Penelitian ini bertujuan untuk menganalisis hubungan dinamis serta meramalkan CAR dan ROA pada Bank BJB tahun 2016–2024 menggunakan model VAR. Data yang digunakan merupakan laporan keuangan triwulanan Bank BJB selama periode tahun 2016 hingga 2024 yang diperoleh melalui website resmi Bank BJB. Data diolah menggunakan software Eviews 10 melalui tahapan statistik deskriptif, uji stasioneritas, uji kointegrasi, estimasi dan stabilitas model, uji diagnostik, penentuan lag optimal, uji kausalitas Granger, peramalan, serta evaluasi akurasi menggunakan nilai MAPE. Hasil menunjukkan bahwa terdapat dua parameter yang signifikan pada taraf nyata 10%, yaitu ΔCAR(-2) terhadap ΔCAR dan ΔROA(-1) terhadap ΔROA. Model peramalan dalam penelitian ini mampu menangkap pola historis CAR dan ROA dengan cukup baik, yang ditunjukkan oleh nilai MAPE sebesar 3,56% untuk CAR yang tergolong sangat baik, dan 22,37% untuk ROA yang berada dalam kategori cukup.